Improvements over time for patients following liver trauma: A 17-year observational study - Brooks, Adam; Joyce, Danielle; La Valle, Angelo; Reilly, John-Joe; Blackburn, Lauren; Kitchen, Samuel; Morris, Louise; Naumann, David N (Frontiers in Surgery, 2023)
BACKGROUND: Centralisation of trauma care has been shown to be associated with improved patient outcomes. The establishment of Major Trauma Centres (MTC) and networks in England in 2012 allowed for centralisation of trauma services and specialties including hepatobiliary surgery. We aimed to investigate the outcomes for patients with hepatic injury over the last 17 years at a large MTC in England in relation to the MTC status of the centre. METHODS: All patients who sustained liver trauma between 2005 and 2022 were identified using the Trauma Audit and Research Network database for a single MTC in the East Midlands. Mortality and complications were compared between patients before and after establishment of MTC status. Multivariable logistic regression models were used to determine the odds ratio (OR) and 95% confidence interval (95% CI) for complications according to MTC status, accounting for the potentially confounding variables of age, sex, severity of injuries and comorbidities for all patients, and the subgroup with severe liver trauma (AAST Grade IV and V). RESULTS: There were 600 patients; the median age was 33 (IQR 22–52) years and 406/600 (68%) were male. There were no significant differences in 90-day mortality or length of stay between the pre- and post-MTC patients. Multivariable logistic regression models showed both lower overall complications (OR 0.24 (95% CI 0.14, 0.39); p<0.001) and lower liver-specific complications (OR 0.21 (95% CI 0.11, 0.39); p<0.001) in the post-MTC period. This was also the case in the severe liver injury subgroup (p=0.008 and p=0.002 respectively). CONCLUSIONS: Outcomes for liver trauma were superior in the post-MTC period even when adjusted for patient and injury characteristics. This was the case even though patients in this period were older with more comorbidities. These data support the centralisation of trauma services for those with liver injuries.